Inhibition of Nf-ҝb prevents trauma-induced heterotopic ossification in rat model. (4th May 2019) - Ju, Jinyong; Yu, Du; Xue, Feng; Zhao, Yong; Shi, Weizhe; Pan, Mingmang; Tang, Guo; Xiao, Haijun
ABSTRACT: Purpose: To investigate the pathogenesis and find a better prophylactic method of acquired heterotopic ossification (HO).Materials and Methods: In the first part, we designed the brain-traumatic/burn/tenotomy rat model and testified its efficacy as HO model. 44 rats were randomly divided into experimental group and control group. After operation, the bilateral tendons of 2 rats were collected at the 2 nd, 3 rd, 4 th, 6 th, 8 th, and 10 th weeks to determine the expression levels of p65. Additionally, the remaining rats were exposed to X-Ray examination at the 10th week. In the second part, 124 rats were randomly divided into four groups based on the administration dosage of Ammonium pyrrolidinedithiocarbamate (PDTC). Then, three rats of each group were euthanized every week in the first seven weeks to collect tendon to detect the expression levels of p65 by qRT-PCR and Western Blot. The remaining rats were exposed to X-Ray examination at the 10th week to assess the size of HO before being euthanized for HE staining.Results: The success rate of Brain-traumatic/Burn/Tenotomy model was 100%. Pharmacologic inhibition of Nf-ҝb signaling pathway by PDTC could significantly reduce the expression levels of p53 and the size of HO, and the reduction was most significant in the 0.6mg dosage group.Conclusions: Brain-traumatic/Burn/Tenotomy model was highly reliable HO model. Inhibition of Nf-ҝb signaling pathway by PDTC could significantly reduce HO formation, and the most effective concentration was 6 mg/ml for local injection.